Primary Myeloid Sarcoma Masquerading as an Obstructing Duodenal Carcinoma - Narayan, Preeti; Murthy, Vijayashree; Su, Mu; Woel, Rosemonde; Grossman, I. Robert; Chamberlain, Ronald S. (Case Reports in Hematology, 2012)
Myeloid Sarcoma (MS), a rare extra hematopoietic carcinoma composed of blast cells, is located primarily in extramedullary sites such as skin, soft tissue, lymph nodes, and bone. MS usually presents in the setting of coexisting acute myeloid leukemia (AML) and myeloproliferative disorders. Gastrointestinal involvement (GI) is extremely rare from nonspecific abdominal symptoms to obstruction. Eight cases of myeloid sarcoma involving the duodenum including the current case have been reported, overall mean age being 40 years (range 17–71) and M : F ratio 7 : 1. The prognosis of patients with de novo MS cases has been reported to be better than those who have a coexisting leukemia. MS is a rare extramedullary tumor, which should be considered in the differential diagnosis of a soft tissue mass involving the duodenum, especially if there is a coexisting hematological disorder. De novo cases often progress to AML, and current therapy involves Daunorubicin- and Cytarabine-based chemotherapy. The wide cytogenetic and molecular heterogeneity of MS implies a potential role for more targeted MS therapies, which may offer a curative strategy.